Dictyna major Menge 1869 - Marusik, Yuri M. (Zenodo, 2022)
Dictyna major Menge, 1869 (Figures 3 a–g, j–k, 4) Dictyna major Menge, 1869: 247, pl. 48, fig. 147 (♂). Dictyna sibirica Kulczyński, 1908: 6, pl. 1, figs 1–2 (D ♀). Syn. nov. Dictyna sibirica simulans Kulczyński, 1916: 1 (♀). Syn. nov. Dictyna hamifera : Eskov 1985: 122 (synonymized with Dictyna sibirica ). Dictyna major : Marusik et al. 2006: 63, figs 1–2 (♀). Dictyna hamifera simulans : WSC 2022. For the complete list of 37 taxonomic references see WSC (2022). Material examined Holotype ♀ of D. sibirica (ZISP), with museum label (Figure 3o): [Yakutia] ‘ Dolgulakh River, tributary of Yana River, 25–26.06/7– 8.07.1885 (Yana Expedition) ’. Syntypes 2♀ of D. s. simulans from Pederata and Kara Rivers with museum label ‘ northwestern Siberia’ (Figure 3h) and original label ‘ Dictyna sibirica var.? simulans , Syberya pn. z’. Comments Dictyna sibirica was previously known only from the original description. Although types of D. sibirica are housed in St. Petersburg, they had never been re-examined. Description of the species was based on an adult specimen from the upper reaches of Dolgulakh (Dulgulakh) River (tributary of Yana River in Yakutia) and a subadult female from Yana River. In the collections of the Zoological Institute in St. Petersburg, there is a vial with ‘ Dictyna sibirica ’ on the label (Figure 3l), containing an adult male and another label in Russian (Figure 3n) with the note ‘1 spider was in jar without tube and label’ and cannot be considered a paratype. Dictyna sibirica was synonymised with D. hamifera Thorell, 1872 by Eskov (1985), although without any justification. Unfortunately, the epigyne was accidentally lost during a photography session. Still, I can confirm that it had the same conformation as those illustrated by Marusik et al. (2006) and Oger (2022) for D. major , and therefore the two names D. sibirica sibirica and D. sibirica simulans are synonymised herein. The epigyne of the syntypes of D. s. simulans (Figure 3a–b, d–e) is identical to that of D. s. sibirica and indistinguishable ...